Impact of valency of a glycoprotein B-specific monoclonal antibody on neutralization of herpes simplex virus - Krawczyk, Adalbert; Krauß, Jürgen; Eis-Hübinger, Anna M.; Däumer, Martin P.; Schwarzenbacher, Robert; Dittmer, Ulf; Schneweis, Karl E.; Jäger, Dirk; Roggendorf, Michael; Arndt, Michaela A. E. (Journal of virology, 2011)
Herpes simplex virus (HSV) glycoprotein B (gB) is an integral part of the multicomponent fusion system required for virus entry and cell-cell fusion. Here we investigated the mechanism of viral neutralization by the monoclonal antibody (MAb) 2c, which specifically recognizes the gB of HSV type 1 (HSV-1) and HSV-2. Binding of MAb 2c to a type-common discontinuous epitope of gB resulted in highly efficient neutralization of HSV at the postbinding/prefusion stage and completely abrogated the viral cell-to-cell spread in vitro. Mapping of the antigenic site recognized by MAb 2c to the recently solved crystal structure of the HSV-1 gB ectodomain revealed that its discontinuous epitope is only partially accessible within the observed multidomain trimer conformation of gB, likely representing its postfusion conformation. To investigate how MAb 2c may interact with gB during membrane fusion, we characterized the properties of monovalent (Fab and scFv) and bivalent [IgG and F(ab′)2] derivatives of MAb 2c. Our data show that the neutralization capacity of MAb 2c is dependent on cross-linkage of gB trimers. As a result, only bivalent derivatives of MAb 2c exhibited high neutralizing activity in vitro. Notably, bivalent MAb 2c not only was capable of preventing mucocutaneous disease in severely immunodeficient NOD/SCID mice upon vaginal HSV-1 challenge but also protected animals even with neuronal HSV infection. We also report for the first time that an anti-gB specific monoclonal antibody prevents HSV-1-induced encephalitis entirely independently from complement activation, antibody-dependent cellular cytotoxicity, and cellular immunity. This indicates the potential for further development of MAb 2c as an anti-HSV drug.
Gesehen am 08.07.2022